3nuts: A Locality-Aware Peer-to-Peer Network Combining Random Networks, Search Trees, and DHTs - Schindelhauer, Christian; Mahlmann, Peter; Janson, Thomas
Categorizing peer-to-peer networks from an algorithmic point of view the two extremes of the spectrum are unstructured networks and networks based on plain distributed hash tables (DHT). Unstructured networks stand out with their simplicity, robustness, and support for complex queries. Though, they lack efficient query algorithms providing guarantees. On the other hand, DHT based networks feature efficient lookup algorithms with typically logarithmic hop distance and provide simple and efficient load balancing. Yet, they are limited to exact match queries and in many cases hard to maintain under churn.

Minimal Energy Path Planning for Wireless Robots - Ooi, Chia Ching; Schindelhauer, Christian (Mobile Networks and Applications (MONET))

Utilizing detours for energy conservation in mobile wireless networks - Ooi, Chia Ching; Schindelhauer, Christian (Telecommunication Systems)

Colouring Non-sparse Random Intersection Graphs - Raptopoulos, Christoforos L.; Nikoletseas, Sotiris E.; Spirakis, Paul G. (34st International Symposium on Mathematical Foundations of Computer Science)

Combinatorial Properties for Efficient Communication in Distributed Networks with Local Interactions - Nikoletseas, Sotiris E.; Raptopoulos, Christoforos L.; Spirakis, Paul G. (Proceedings of IPDPS - IEEE International Parallel & Distributed Processing Symposium)

Distributed Heterogeneous Hashing and Deterministic Dynamical Decompositions - Deveci, Deniz; Kortenjan, Michael; Schomaker, Gunnar (Parallel and Distributed Computing and Systems, Nr. 21)

Analysis and implementation of an Artificial Homeostatic Hormone System: A first case study in robotic hardware - Stradner, Jürgen; Hamann, Heiko; Schmickl, Thomas; Crailsheim, Karl (2009 IEEE/RSJ International Conference on Intelligent Robots and Systems)
One of the prominent challenges in mobile robotics is to develop control methodologies that allow the adaptation to dynamic and unforeseen environments. The classic approach of hand-coded controllers is very efficient for well-defined tasks and specific environments but poor in adapting to changing environmental conditions. One alternative approach is the application of evolutionary algorithms which need, in turn, easily evolvable representations of controllers. In this paper, we investigate one promising approach of an artificial hormone system as a control paradigm which is believed to be easily optimized by evolutionary processes. In a first step of this research, we focus on the simple task of collision avoidance. We present a brief mathematical analysis of this controller approach and an implementation of the controller on a mobile robot to check the feasibility in principle of our approach. The task is successfully accomplished and we conclude with a discussion of the hormone dynamics in the robot.

Two different approaches to a macroscopic model of a bio-inspired robotic swarm - Schmickl, Thomas; Hamann, Heiko; Wörn, Heinz; Crailsheim, Karl (Robotics and Autonomous Systems)
By compiling macroscopic models we analyze the adaptive behavior in a swarm of autonomous robots generated by a bio-inspired, distributed control algorithm. We developed two macroscopic models by taking two different perspectives: A Stock & Flow model, which is simple to implement and fast to simulate, and a spatially resolved model based on diffusion processes. These two models were compared concerning their prediction quality and their analytical power: One model allowed easy identification of the major feedback loops governing the swarm behavior. The other model allowed analysis of the expected shapes and positions of observable robot clusters. We found a high correlation in the challenges posed by both modeling techniques and we highlighted the inherent problems of inferring emergent macroscopic rules from a microscopic description of swarm behavior.

Pattern Formation as a Transient Phenomenon in the Nonlinear Dynamics of a Multi-Agent System - Hamann, Heiko; Troch, Inge; Breitenecker, F. (MATHMOD 2009 - 6th Vienna International Conference on Mathematical Modelling)

Compositional CSP Traces Refinement Checking - Wehrheim, Heike; Wonisch, Daniel (Electr. Notes Theor. Comput. Sci.)

Static Class Elements for Object-Z - Ruhroth, Thomas; Wehrheim, Heike (Electr. Notes Theor. Comput. Sci.)

Measure, Diagnose, Refactor: A Formal Quality Cycle for Software Models - Ruhroth, Thomas; Voigt, Hendrik; Wehrheim, Heike (35th Euromicro Conference on Software Engineering and Advanced Applications, SEAA 2009, Patras, Greece, August 27-29, 2009, Proceedings)

Integrated Formal Methods, 7th International Conference, IFM 2009, Düsseldorf, Germany, February 16-19, 2009. Proceedings

Hierarchisches Clustering mit minimalen Cluster-Durchmessern - Schröer, Carsten

Analyse und Evaluation eines identitätsbasierten Signcryption-Verfahrens - Liske, Gennadij

Die Schwierigkeit des k-Median Clusterings für Bregman-Divergenzen - Scholz, Christoph

Algorithms for the Bregman k-Median Problem - Ackermann, Marcel Rudolf

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Coresets and Approximate Clustering for Bregman Divergences - Ackermann, Marcel R.; Blömer, Johannes (Proceedings of the Twentieth Annual ACM-SIAM Symposium on Discrete Algorithms)

Sampling methods for shortest vectors, closest vectors and successive minima - Blömer, Johannes; Naewe, Stefanie (Theoretical Computer Science)
Keywords: Geometry of numbers; Lattices; Shortest vectors

Three-Valued Spotlight Abstractions - Schrieb, Jonas; Wehrheim, Heike; Wonisch, Daniel (FM 2009: Formal Methods)

On the Analysis of Cryptographic Assumptions in the Generic Ring Model - Jager, Tibor; Schwenk, Jörg (Advances in Cryptology - ASIACRYPT 2009, 15th International Conference on the Theory and Application of Cryptology and Information Security, Tokyo, Japan, December 6-10, 2009. Proceedings)

Musterbasiertes Re-Engineering von Softwaresystemen - Meyer, Matthias

Self-Organisation and Self-Optimization - Meyer auf der Heide, Friedhelm; Rammig, Franz-Josef (Public Service Review: Science and Technology)

Algorithmische und komplexitätstheoretische Aspekte kombinatorischer Preisoptimierung (Computational Aspects of Combinatorial Pricing Problems) - Briest, Patrick (it - Information Technology)

Foreword - D. Kleinberg, Robert; Scheideler, Christian (Theory Comput. Syst.)

Towards a Scalable and Robust DHT - Awerbuch, Baruch; Scheideler, Christian (Theory Comput. Syst.)

Robust random number generation for peer-to-peer systems - Awerbuch, Baruch; Scheideler, Christian (Theor. Comput. Sci.)

A Distributed and Oblivious Heap - Scheideler, Christian; Schmid, Stefan (Automata, Languages and Programming, 36th Internatilonal Colloquium, ICALP 2009, Rhodes, Greece, July 5-12, 2009, Proceedings, Part II)

A Self-stabilizing and Local Delaunay Graph Construction - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Algorithms and Computation, 20th International Symposium, ISAAC 2009, Honolulu, Hawaii, USA, December 16-18, 2009. Proceedings)

A distributed polylogarithmic time algorithm for self-stabilizing skip graphs - Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Proceedings of the 28th Annual ACM Symposium on Principles of Distributed Computing, PODC 2009, Calgary, Alberta, Canada, August 10-12, 2009)

A DoS-resilient information system for dynamic data management - Baumgart, Matthias; Scheideler, Christian; Schmid, Stefan (SPAA 2009: Proceedings of the 21st Annual ACM Symposium on Parallelism in Algorithms and Architectures, Calgary, Alberta, Canada, August 11-13, 2009)

Brief Announcement: On the Time Complexity of Distributed Topological Self-stabilization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Stabilization, Safety, and Security of Distributed Systems, 11th International Symposium, SSS 2009, Lyon, France, November 3-6, 2009. Proceedings)

Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Algorithmic Methods for Distributed Cooperative Systems, 06.09. - 11.09.2009)

Rupeas: Ruby Powered Event Analysis DSL - Woehrle, Matthias; Plessl, Christian; Thiele, Lothar
Wireless Sensor Networks (WSNs) are unique embedded computation systems for distributed sensing of a dispersed phenomenon. While being a strongly concurrent distributed system, its embedded aspects with severe resource limitations and the wireless communication requires a fusion of technologies and methodologies from very different fields. As WSNs are deployed in remote locations for long-term unattended operation, assurance of correct functioning of the system is of prime concern. Thus, the design and development of WSNs requires specialized tools to allow for testing and debugging the system. To this end, we present a framework for analyzing and checking WSNs based on collected events during system operation. It allows for abstracting from the event trace by means of behavioral queries and uses assertions for checking the accordance of an execution to its specification. The framework is independent from WSN test platforms, applications and logging semantics and thus generally applicable for analyzing event logs of WSN test executions.
Keywords: Rupeas; DSL; WSN; testing

On Stackelberg Pricing with Computationally Bounded Consumers - Briest, Patrick; Hoefer, Martin; Gualà, Luciano; Ventre, Carmine (Lecture Notes in Computer Science)
In a Stackelberg pricing game a leader aims to set prices on a subset of a given collection of items, such as to maximize her revenue from a follower purchasing a feasible subset of the items. We focus on the case of computationally bounded followers who cannot optimize exactly over the range of all feasible subsets, but apply some publicly known algorithm to determine the set of items to purchase. This corresponds to general multi-dimensional pricing assuming that consumers cannot optimize over the full domain of their valuation functions but still aim to act rationally to the best of their ability. We consider two versions of this novel type of Stackelberg pricing games. Assuming that items are weighted objects and the follower seeks to purchase a min-cost selection of objects of some minimum weight (the Min-Knapsack problem) and uses a simple greedy 2-approximate algorithm, we show how an extension of the known single-price algorithm can be used to derive a polynomial-time (2 + ε)-approximation algorithm for the leader’s revenue maximization problem based on so-called near-uniform price assignments. We also prove the problem to be strongly NP-hard. Considering the case that items are subsets of some ground set which the follower seeks to cover (the Set-Cover problem) via a standard primal-dual approach, we prove that near-uniform price assignments fail to yield a good approximation guarantee. However, in the special case of elements with frequency 2 (the Vertex-Cover problem) it turns out that exact revenue maximization can be done in polynomial-time. This stands in sharp contrast to the fact that revenue maximization becomes APX-hard already for elements with frequency 3.

Concepts for Model Verification and Validation during Simulation Runtime - Laroque, Christoph; Fischer, Matthias; Dangelmaier, Wilhelm (European Simulation and Modelling Conference (ESM 2009))
Modern companies are nowadays confronted with an increasing demand of multiple products, where they need to perform more flexible every day. Cost-intensive decisions are to be confirmed in short times, in order to minimize risks and secure efficient production programs as well as material flows. Tools for this digital planning via simulation methods are one well established possibility to receive decision support. Nevertheless, the creation of the necessary simulation models is a complicated and error-prone process, where complexity of modeling, validation and verification depends on the used tool and its functionalities. This paper presents implemented concepts for an innovative user support in his tasks of verification and validation of simulation models during the execution of a simulation run. Time-intensive procedures like stopping simulation, parameterization and restarting within the problem analysis are simplified. So the user is able to focus on the real problem solving task.

Improving Network Coded Cooperation by Soft Information - Volkhausen, Tobias; Woldegebreal, Dereje H.; Karl, Holger (2009 6th IEEE Annual Communications Society Conference on Sensor, Mesh and Ad Hoc Communications and Networks Workshops)

Combining for Cooperative WLANs - A Reality Check Based on Prototype Measurements - Valentin, S.; Woldegebreal, D. H.; Volkhausen, T.; Karl, Holger (2009 IEEE International Conference on Communications Workshops)

Ein System zur aggregierten Visualisierung verteilter Materialflusssimulationen - Suess, Tim; Fischer, Matthias; Huber, Daniel; Laroque, Christoph; Dangelmaier, Wilhelm (Augmented & Virtual Reality in der Produktentstehung)

Creating Butterflies in the Core – A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009)

Modeling obstacles in INET/Mobility framework: motivation, integration, and performance - Lichte, Hermann S.; Weide, Jannis (Proceedings of the Second International ICST Conference on Simulation Tools and Techniques)

Design considerations for a network of information - Ahlgren, Bengt; Vercellone, Vinicio; D'Ambrosio, Matteo; Marchisio, Marco; Marsh, Ian; Dannewitz, Christian; Ohlman, Börje; Pentikousis, Kostas; Strandberg, Ove; Rembarz, René (Proceedings of the 2008 ACM CoNEXT Conference on - CONEXT '08)

Planar Visibility Counting - Fischer, Matthias; Hilbig, Matthias; Jähn, Claudius; Meyer auf der Heide, Friedhelm; Ziegler, Martin (Proc. 25th European Workshop on Computational Geometry)
For a fixed virtual scene (=collection of simplices) S and given observer position p, how many elements of S are weakly visible (i.e. not fully occluded by others) from p? The present work explores the trade-off between query time and preprocessing space for these quantities in 2D: exactly, in the approximate deterministic, and in the probabilistic sense. We deduce the EXISTENCE of an O(m^2/n^2) space data structure for S that, given p and time O(log n), allows to approximate the ratio of occluded segments up to arbitrary constant absolute error; here m denotes the size of the Visibility Graph--which may be quadratic, but typically is just linear in the size n of the scene S. On the other hand, we present a data structure CONSTRUCTIBLE in O(n*log(n)+m^2*polylog(n)/k) preprocessing time and space with similar approximation properties and query time O(k*polylog n), where k<n is an arbitrary parameter. We describe an implementation of this approach and demonstrate the practical benefit of the parameter k to trade memory for query time in an empirical evaluation on three classes of benchmark scenes.

Solution Patterns for the Development of Self-Optimizing Systems - Dumitrescu, Roman; Gausemeier, Jürgen; Dangelmaier, Wilhelm; Klöpper, Benjamin (Self-x in Engineering)

Education Programme at Eurographics 2009 - Domik, Gitta; Scateni, Riccardo (Computer Graphics Forum)

Quantitative myocardial perfusion PET combined with coronary anatomy derived from CT angiography: Validation of a new fusion and visualisation software - Fricke, Harald; Elsner, Andreas; Weise, Reiner; Bolte, Matthias; van den Hoff, Jörg; Burchert, Wolfgang; Domik, Gitta; Fricke, Eva (Zeitschrift für Medizinische Physik)
Keywords: Coronary artery disease; CT angiography; cardiac PET; quantitative perfusion measurement; Koronare Herzerkrankung; CT-Angiographie; PET; quantitative Perfusionsmessung

Proceedings of the Workshop on Model Driven Development of Advanced User Interfaces (MDDAUI'09), Sanibel Island (FL, USA)

Proceedings of Design for Future - 1. Workshop des GI-Arbeitskreises "Langlebige Softwaresysteme (L2S2)"

Language-Independent Change Management of Process Models - Gerth, Christian; Küster, Jochen; Engels, Gregor (Proceedings of the ACM/IEEE 12th International Conference on Model Driven Engineering Languages and Systems (MODELS'09). Denver (CO, USA))
In model-driven development approaches, process models are used at different levels of abstraction and are described by different languages. Similar to other software artifacts, process models are developed in team environments and underlie constant change. This requires reusable techniques for the detection of changes between different process models and the computation of dependencies and conflicts between changes. In this paper, we propose a framework for the construction of process model change management solutions that provides generic techniques for the detection of differences and the computation of dependencies and conflicts between changes. The framework contains an abstract representation for process models that serves as a common denominator for different process models. In addition, we show how the framework is instantiated exemplarily for BPMN.

SOA-Business Case - Assmann, Martin; Haack, Markus; Scheider, Hendrik; vom Hagen, Nico; Zacharias, Roger (Transform IT: Optimale Geschäftsprozesse durch eine transformierende IT)

A Holistic Software Engineering Method for Service-Oriented Application Landscape Development - Baumann, Andrea; Engels, Gregor; Hofmann, Alexander; Sauer, Stefan; Willkomm, Johannes (Proceedings of the First NAF Academy Working Conference on Practice-Driven Research on Enterprise Transformation (PRET 2009), Amsterdam (The Netherlands))
Enterprises are transforming into enterprises which follow from a business as well as from an IT perspective a service-oriented paradigm. This change towards service-oriented enterprise and IT architectures has to be reflected in the methodologies of developing whole application landscapes as well as individual applications. Quasar (Quality Software Architecture) has been developed as the standard architecture and development method of Capgemini sd&m for individual applications. For the development of service-oriented enterprise application landscapes, Quasar Enterprise has been designed. Both Quasar and Quasar Enterprise are integrated with each other within a holistic software engineering method to seamlessly cover the full development lifecycle of service-oriented application landscapes, from business modeling and service design to actual software development. In this paper, we illustrate how a company-wide ontology of development artifacts serves as the key feature for integrating both methods.

Model Driven Development of Advanced User Interfaces 2009 - Meixner, Gerrit; Görlich, Daniel; Breiner, Kai; Hußmann, Heinrich; Pleuß, Andreas; Sauer, Stefan; Van den Bergh, Jan (Proceedings of the 2009 International Conference on Intelligent User Interfaces)

Dependent and Conflicting Change Operations of Process Models - Küster, Jochen; Gerth, Christian; Engels, Gregor (Proceedings of the 5th European Conference on Model-Driven Architecture Foundations and Applications (ECMDA-FA'09))
Version management of models is common for structural diagrams such as class diagrams but still challenging for behavioral models such as process models. For process models, conflicts of change operations are difficult to resolve because often dependencies to other change operations exist. As a consequence, conflicts and dependencies between change operations must be computed and shown to the user who can then take them into account while creating a consolidated version. In this paper, we introduce the concepts of dependencies and conflicts of change operations for process models and provide a method how to compute them. We then discuss different possibilities for resolving conflicts. Using our approach it is possible to enable version management of process models with minimal manual intervention of the user.

Sicherstellen der Betrachtung von nicht-funktionalen Anforderungen in SCRUM-Prozessen durch Etablierung von Feedback - Engels, Gregor; Geisen, Silke; Sauer, Stefan; Port, Olaf (Informatik 2009 - Im Focus das Leben)

Integrated Specification and Quality Assurance for Large Business Information Systems - Salger, Frank; Sauer, Stefan; Engels, Gregor (Proceedings of the 2nd India Software Engineering Conference (ISEC'09))

Model-Based System Testing Using Visual Contracts - Güldali, Baris; Mlynarski, Michael; Wübbeke, Andreas; Engels, Gregor (Proceedings of Euromicro SEAA Conference 2009, Special Session on “Model Driven Engineering”)

Zautomatyzowane testy akceptacyjne dla aplikacji internetowych w programowaniu sterowanym testami - Mlynarski, Michael; Jureczko, Marian (Proceedings of Krajowa Konferencja In?ynierii Oprogramowania 2009)

A UML Framework for IP-XACT-based IP Management - Schattkowsky, Tim; Xie, Tao (Proceedings of the conference on Design Automation and Test in Europe (DATE 2009), Nice (France))

Towards Test-Driven Semantics Specification - Soltenborn, Christian; Engels, Gregor (Proceedings of the 12th International Conference on Model Driven Engineering Languages and Systems (MODELS 2009), Denver, Colorado (USA))
Behavioral models are getting more and more important within the software development cycle. To get the most use out of them, their behavior should be defined formally. As a result, many approaches exist which aim at specifying formal semantics for behavioral languages (e.g., Dynamic Meta Modeling (DMM), Semantic Anchoring). Most of these approaches give rise to a formal semantics which can e.g. be used to check the quality of a particular language instance, for instance using model checking techniques. However, if the semantics specification itself contains errors, it is more or less useless, since one cannot rely on the analysis results. Therefore, the language engineer must make sure that the semantics he develops is of the highest quality possible. To help the language engineer to achieve that goal, we propose a test-driven semantics specification process: the semantics of the language under consideration is first informally demonstrated using example models, which will then be used as test cases during the actual semantics specification process. In this paper, we present this approach using the already mentioned specification language DMM.

Improving Reusability of Dynamic Meta Modeling Specifications with Rule Overriding - Engels, Gregor; Fisseler, Daniela; Soltenborn, Christian (Proceedings of the 2009 IEEE Symposium on Visual Languages and Human-Centric Computing (VL/HCC 2009), Corvallis, Oregon (USA))

Semi-automated Test Planning for e-ID Systems by Using Requirements Clustering - Güldali, Baris; Funke, Holger; Jahnich, Michael; Sauer, Stefan; Engels, Gregor (24th IEEE/ACM International Conference on Automated Software Engineering (ASE 2009), 16-20 November 2009, Auckland, New Zeland)
In acceptance testing, customer requirements as specified in system specifications have to be tested for their successful implementation. This is a time-consuming task due to inherent system complexity and thus a large number of requirements. In order to reduce efforts in acceptance testing, we introduce a novel approach that exploits redundancies and implicit relations in requirements specifications, which are based on multi-viewpoint techniques, in our case the reference model for open distributed processing (RM-ODP). It deploys requirements clustering and linguistic analysis techniques for reducing the total number of test cases. We report on concrete experiences with this approach within joint R&D work of the Software Quality Lab (s-lab) of the University of Paderborn and HJP Consulting, an international consulting company, specialized in planning, procurement and acceptance testing of national electronic identification (e-ID) systems. The paper is concluded with an overview on the current tool support especially for automated detection of the redundancies and implicit relations in requirements. Also the future work on the tool support for the overall test specification process is discussed.

Identifying Software Product Line Component Services - Assmann, Martin; Engels, Gregor; von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of International Conference on Evaluation of Novel Approaches to Software Engineering (ENASE 09))

Flow Synchronization for Network Coding - Biermann, Thorsten; Dräxler, Martin; Karl, Holger (Journal of Communications)

Cooperative Wireless Networking Beyond Store-and-Forward - Valentin, Stefan; S. Lichte, Hermann; Karl, Holger; Vivier, Guillaume; Simoens, Sebastien; Vidal, Josep; Agustin, Adrian (Wireless Personal Communications)

An Adaptive Resource/Performance Trade-Off for Resolving Complex Queries in P2P Networks - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Proceedings of IEEE International Conference on Communications, ICC 2009, Dresden, Germany, 14-18 June 2009)

Rate-Per-Link Adaptation in Cooperative Wireless Networks with Multi-Rate Combining - S. Lichte, Hermann; Valentin, Stefan; von Malm, Holger; Karl, Holger; Bin Sediq, Akram; Aad, Imad (Proceedings of IEEE International Conference on Communications, ICC 2009, Dresden, Germany, 14-18 June 2009)

The Gain of Overbooking - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing, 14th International Workshop, JSSPP 2009, Rome, Italy, May 29, 2009. Revised Papers)

Analyzing space/capacity tradeoffs of cooperative wireless networks using a probabilistic model of interference - Simon Lichte, Hermann; Valentin, Stefan; Karl, Holger; Aad, Imad; Widmer, J. (Proceedings of the 12th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2009, Tenerife, Canary Islands, Spain, October 26-19, 2009)

Creating Butterflies in the Core - A Network Coding Extension for MPLS/RSVP-TE - Biermann, Thorsten; Schwabe, Arne; Karl, Holger (NETWORKING 2009, 8th International IFIP-TC 6 Networking Conference, Aachen, Germany, May 11-15, 2009. Proceedings)

A virtual network mapping algorithm based on subgraph isomorphism detection - Lischka, Jens; Karl, Holger (Proceedings of the 1st ACM SIGCOMM Workshop on Virtualized Infrastructure Systems and Architectures, VISA 2009, Barcelona, Spain, August 17, 2009)

“Metriken” – Kennzahlen zur Verbesserung der Softwarequalität, Teile 1 und 2 - Gehrke, Matthias; Güldali, Baris; Meyer, Jan; Sancar, Yavuz; Spijkerman, Michael

"Metriken" - Kennzahlen zur Verbesserung der Softwarequalität, Teile 1 und 2 - Gehrke, Matthias; Güldali, Baris; Meyer, Jan; Sancar, Yavuz; Spijkerman, Michael

Evaluierung von Bewertungsmodellen für den Testprozess - Yigitbas, Enes

Guest Editorial to the Special Section on MODELS 2007 - Engels, Gregor (Software & Systems Modeling)

Modellbasiertes Testen auf Basis des fundamentalen Testprozesses - Spijkerman, Michael; Eckardt, Tobias (Softwaretechnik-Trends)

A Holistic Software Engineering Method for Service-Oriented Application Landscape Development - Sauer, Stefan; Engels, Gregor; Willkomm, Johannes; Baumann, Andrea; Hofmann, Alexander (Advances in Enterprise Engineering II)

Design for Future – Legacy-Probleme von morgen vermeidbar? - Engels, Gregor; Goedicke, Michael; Goltz, Ursula; Rausch, Andreas; Reussner, Ralf (Informatik-Spektrum)

Kontextsensitive Qualitätsplanung von Softwaremodellen - Voigt, Hendrik
The Model Quality Plan (MQP) approach provided by us allows for the systematic and efficient development of quality plans that serve as a basis for the assessment of software models. MQP emphasizes the context of a software model as a major factor of influence for the whole quality planning activity. In order to adjust a quality plan to project specific requirements, quality goals are derived from a characterization of that context. We achieve a differentiated description of quality goals by introducing structured goals and questions in combination with a defined quality model. Afterwards, metrics and indicators are identified for checking the fulfillment of the quality goals. The result of our approach consists of a context sensitive quality plan for software models. Conceptually, we combine a metamodel for formulating relevant contents, a process that serves as a guideline for defining quality plans, and a rule concept for packaging and reusing experience into an integrated framework. We show its feasibility by three case studies that include a quality plan for analysis models, design models, and test models, respectively. For that, we provide tool support for the definition and application of quality plans.

Platform independent modeling of synthesizable software systems using UML 2 - Schattkowsky, Tim

Pattern based business process design and verification - Förster, Alexander

Model-based evaluation of service-oriented enterprise architectures - Assmann, Martin
Enterprise Architecture (EA) has undergone many changes since the IT has found its way into the world of enterprises. The introduction of Service-Oriented Architecture (SOA) is such a change with major consequences. The introduction of an SOA increases the flexibility and thus the productivity of an enterprise architecture, but unfortunately also its complexity. This makes the transformation of an enterprise architecture to an SOA-like enterprise architecture to a challenging and risky task. To overcome the change- and complexity-related problems when introducing SOA, Enterprise Architecture Management (EAM) systems are required. The approach of this thesis suggests a method on how to establish Enterprise Architecture Management that is especially suited for an SOA introduction. This thesis suggests a variant of an EAM system that is especially suited for the introduction of an SOA. The presented method on creating such an EAM system includes guidance on how to define a meta model for Service-Oriented Enterprise Architecture (SOEA), which is harmonized with the respective enterprise architecture. The SOA introduction is especially supported by defining SOA quality criteria and corresponding metrics. Some metrics have to be ascertained by experts. Other metrics have their measuring points within the SOEA models (instances of the SOEA meta model) and their calculation is automatable. Creating and maintaining SOEA models as well as applying the automatable metrics are supported by an eclipse-based tool. As metrics only produce measures that are hard to interpret, indicators are introduced. They allow interpreting the measures concerning the quality criteria. With the help of this EAM system, the transformation of an enterprise to a service-oriented enterprise can be planned and the level of goal-achievement (SOA-conformance of the EA) can be monitored steadily. By this, the contribution of this work aims at the reduction of the risk when introducing an SOA.

From Design Models to Test Models by Means of Test Ideas - Mlynarski, Michael; Güldali, Baris; Späth, Melanie; Engels, Gregor (MoDeVVa '09: Proceedings of the 6th International Workshop on Model-Driven Engineering, Verification and Validation)

Automatic Generation of Behavioral Code - too ambitious or even unwanted? - Engels, Gregor (First European Workshop on Behaviour Modelling in Model Driven Architecture (BM-MDA))

Inspection Effectiveness for Different Quality Attributes of Software Requirement Specifications - An Industrial Case Study - Salger, Frank; Engels, Gregor; Hofmann, Alexander (Proceedings of the ICSE Workshop on Software Quality (WoSQ 2009))

An Integrated Quality Assurance Framework for Specifying Business Information Systems - Salger, Frank; Sauer, Stefan; Engels, Gregor (Proceedings of the Forum at the CAiSE 2009 Conference, Amsterdam (The Netherlands))
The software specification acts as a bridge between customers, architects, software developers and testers. If information gets lost or distorted when building this bridge, the wrong system will be built or the system will not be built in time and budget–or both! Standards and recommendations give advice on how to structure specifications or check software-engineering artefacts with reviews or inspections. But these constructive and analytical approaches are not well integrated with each other. Moreover, they are often too generic to efficiently support the specification of particular system types. In this paper, we present the integrated “specification framework” of Capgemini sd&m. It consists of our specification method for business information systems (BIS) and its concerted analytical counterpart, the “specification quality gate”. Since this framework is tailored to the specification of large BIS, it allows a quick ramp-up phase for software engineering projects without the need for extensive tailoring or extension.

Towards Generalizing Visual Process Pattern - Soltenborn, Christian; Engels, Gregor (Proceedings of the 1st International Workshop on Visual Formalisms for Patterns (VFfP 2009), Corvallis, OR (USA))
Visual Process Pattern (VPP) is a visual language to describe constraints on the behavior of UML Activities. They have been developed for the sake of formulating and verifying requirements on business process models (with Activities being one possible description language). In the VPP approach, a visual pattern is translated into an LTL formula, which can then be verified against a transition system describing the behavior of the Activity under consideration. In this paper, we aim at generalizing VPP. We show how to formulate patterns more generally, using either concrete or abstract syntax of the behavioral model under consideration. Additionally, we describe how these more general patterns can be verified against a model’s behavior.

Lösungsorientierte Software Produktlinienentwicklung in heterogenen Systemlandschaften - von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of Produktlinien im Kontext (PIK09))

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Optimal strategies for maintaining a chain of relays between an explorer and a base camp - Kutyłowski, Jarosław; Meyer auf der Heide, Friedhelm (Theoretical Computer Science)

Power-aware online file allocation in mobile ad hoc networks - Mehler, Jan; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-first annual symposium on Parallelism in algorithms and architectures - SPAA '09)

Proceedings of the twenty-first annual symposium on Parallelism in algorithms and architectures - SPAA '09

Who is on my Team: Building strong Teams in Interdisciplinary Visualization Courses - Domik, Gitta (ACM SIGGRAPH ASIA 2009 Educators Program)

Towards multi-movement hand prostheses: Combining adaptive classification with high precision sockets - Boschmann, Alexander; Kaufmann, Paul; Platzner, Marco; Winkler, Michael (Proc. Technically Assisted Rehabilitation (TAR))

Evolvable Robot Controller - Kostin, Alexander

ReconOS: Multithreaded Programming for Reconfigurable Computers - Lübbers, Enno; Platzner, Marco (ACM Transactions on Embedded Computing Systems)
Keywords: Reconfigurable computing; multithreading; operating systems

Compiler for a Custom Instruction Set CPU - Tofall, Martin

Coarse-grained CGP Model using Xilinx Virtex5 DSP48E Functional Units - Warkentin, Alexander

Implementierung von Kryptographie-Hardwarebeschleunigern für das HW/SW-Betriebssystem ReconOS - Wildenhain, Benedikt

Signature Self Checking (SSC): A Low-Cost Reliable Control Logic for Pipelined Microprocessors - Ghasemzadeh Mohammadi, Hassan; Miremadi, Seyed Ghassem; Ejlali, Alireza (Dependable Computing (PRDC), 2009 IEEE Pacific Rim International Symposium on)